SAHAR: a control plane architecture for high available software-defined networks. (24th April 2020) - Shetabi, Mehran; Akbari, Ahmad
Software-defined networking (SDN) is an architectural paradigm which enables a centralised control by decoupling the data and control planes of a network. In reactive mode of SDN, the significant variation in flow arrival events places considerable stress on the control plane. Also, the existence of frequent events such as network-wide statistics collection which significantly interfere with the basic functions of control plane can drastically affect performance of control plane. Therefore, this paper introduces a new architectural model named SAHAR that uses a controller box consisting of a coordinator controller and a primary flow-setup controller and one or more secondary flow-setup controllers as needed. Assigning monitor and management tasks to the coordinator controller reduces the load on the flowsetup controllers. Also, dividing input traffic between flow-setup controllers by the coordinator controller distributes the load in the control plane. In this way, SAHAR achieves a high available SDN which can be scalable.